Echogenicity of the Carotid Arterial Wall in Active Smokers. (May 2018) - Mitchell, Carol; Piper, Megan E.; Korcarz, Claudia E.; Hansen, Kristin; Weber, JoAnne; Fiore, Michael C.; Baker, Timothy B.; Stein, James H.
This pilot study evaluated associations between carotid wall echogenicity, cardiovascular disease (CVD) risk factors, and three markers of smoking heaviness in a cohort of active smokers. Common carotid artery (CCA) gray-scale median (GSM) values were measured from sonographic images. Univariable correlations and exploratory multivariable models were used to determine associations between CCA GSM, CVD risk factors, and measures of smoking heaviness. CCA GSM was measured in 162 smokers and was correlated inversely with cigarettes smoked/d (r = −0.16, P = .048); pack-years (r = −0.204, P = .009); CVD risk factors such as age, male sex, waist circumference, and low-density lipoprotein cholesterol (all P ≤ .03); and positively with high-density lipoprotein cholesterol ( P < .001). Associations between CCA GSM and smoking heaviness markers were not statistically significant after adjustment for traditional risk factors. The results from this pilot study demonstrate the feasibility of measuring the GSM value of the CCA far wall and its association with measures of smoking heaviness and traditional CVD risk factors among current smokers.